Obravnava starostnika v družinski medicini - Petek Šter, Marija (Zdravniški vestnik, 2004)
Background. The number of elderly patients, i.e. people over 64 years, is growing. With longer life span the proportion of elderly people will be even higher Elderly patients are a heterogeneous group of patients with considerable differences in health status, functional capacity, emotions, fears, beliefs and views. Health care of elderly patients in primary care is aresponsibility of family doctors. One third of all family practice consultations are in the age group over 64. A consultation in the elderly is different from a consultation in younger patients. The consultation length in those patients is longer and the office visits of elderly are more frequent Ifwe want to deliver a quality care for the elderly, we have to care for them and manage their illness in psychological, physical, family and social context, which is a core stone of biopsychosocial model of medical practice. Besides medical knowledge and patient participation, all these elements make afoundation of the holistic approach. In elderly a special attention to their attitude towards aging, dying, loneliness and to the fears connected to those issues should be taken into account Coordination with other services and with patients' families is also necessary. Family physician is in the best positionto recognise abuse, neglection or limitations in patient autonomy. We should be aiming to achieve a connection between the doctor and the patient through continuity between the doctor, the patient and his/her family. Good connection will make management of elderly patients more effective and the patients will accept and follow therapeutic plan.
Keywords: Aged; chronic condition; Chronic Disease; Demenca; Dementia; Družinska medicina; Družinsko zdravje; Duševne motnje; Family Health; Family Practice; Kronična bolezen; Mental Disorders; Organization And Administration; Physician-Patient Relations; Physician'S Role; Social Problems; Socialni problemi; Starostniki; therapy; zdravljenje; Zdravnik-bolnik, odnosi; Zdravnikova vloga